Implementation of Age Replacement Method for Molding Machine Maintenance at PT. KMI - Yudhanto, Djovanka Arya Putra; Febryanto, Indra Dwi; Prihono (Tibuana, 2025)
The rapid development of the industrial world has caused the manufacturing industry to think hard to survive the fierce competition. PT. KMI is a company engaged in industrial furniture, oriented to the best quality in its products and supported by sophisticated technology in the production process. The problem that occurs is unexpected machine damage causing the production process to stop. The way to overcome this is to schedule the replacement of components that are susceptible to damage, especially sensors, bearings and roller trans. Determination of critical components using the ABC method and the age replacement method. The selection of damage distribution, at this stage is based on the goodness of fit value. One way to increase productivity is to schedule the replacement of components that are susceptible to damage, especially sensors, bearings and roller trans. The recommended replacement time is 128 days for sensors with a cost reduction of IDR 1.848.097 for replacement of sensor components, 261 days for bearing components with a cost reduction of IDR 1.301.553 and 251 days for roller trans components with a cost reduction of IDR 1.646.870. by using the ABC method, 3 critical components can be found, namely sensors and bearings with a percentage value of 42.80% for sensors, 20.95% for bearings, and 14.03% for Roller trans. The most optimal time interval for the three components is the sensor component 128 days with downtime cost savings of IDR 1.848.097. The bearing component 261 days with downtime cost savings of IDR 1.301.553. The roller trans component 251 days with downtime cost savings of IDR 1.646.870.